The Students Perception of the Use Cornell-Note Taking Method in Improving Reading Retention at SMPN 1 Segeri - Patty, Rafiqa Salwa; Abdullah, Abdullah; Munir, Munir (Yayasan Ahmar Cendekia Indonesia, 2025)
This study aimed to determine students’ perception of the use of the Cornell note-taking method in improving reading retention. The theories underlying this research were Organizational Behaviour Theory, as presented by Robbins (2003), and the perception framework proposed by Kiong (2009), which highlights three key indicators of perception: acceptance, understanding, and assessment. Data were collected through interviews; this research applied a stratified purposive sampling technique. Participants were selected based on their post-test performance, which was categorized into students who had the best scores after conducting the post-test at SMPN 1 Segeri. Findings revealed that students’ perceptions of using the Cornell Note-taking method to improve reading retention had a positive perception. The study recommends that students, teachers, and future researchers investigate other methods that can improve reading retention and investigate the long-term effects of using the Cornell note-taking method at various educational levels, such as senior high school or university.